Analisis Efisiensi Pemasaran Bawang Merah Di Kecamatan Sape Kabupaten Bima - Dm. Ali, Miftahul Khairat; Hayati, Hayati; Sjah, Taslim (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
The aims of this research were to describe and analyze the marketing efficiency of red onion in Sape District, Bima Regency. This research was conducted in Naru Village from November to December 2023 taking into account that Naru Village is one of the red onion producing areas in Sape District, Bima Regency. The sample of farmers and institutions in the research was determined using the snowball sampling method, by searching through marketing channels. The survey was conducted by interviewing these samples The marketing institute for this research was chosen based on the sales flow of red onion in Naru Village, Sape District, Bima Regency. The data collected form primary data and secondary data. From the survey results, it is known that (1) the sales channels of red onion in Naru Village, Sape District, Bima Regency are farmers, collectors, and wholesalers; (2) Marketing margin at the collecting merchant level of 5,000 rupiah per kilogram and marketing margin at the wholesaler level of 3,000 rupiah per kg. (3) The sales efficiency value at the collector level and wholesaler level is efficient, and the red onion sales efficiency value is 3% at the collector level and 5% at the wholesaler level.